DEPRESSÃO PÓS-PARTO: Impactos no desenvolvimento infantil e nas relações familiares (REMUNOM, 2025)
Depression is an alteration in brain function that affects an individual's behavior, mood, and cognitive and hormonal functions. The DSM-5-TR includes postpartum depression as a specifier of Major Depressive Disorder, with initial mood symptoms occurring during pregnancy or within four weeks postpartum. This article aims to understand how postpartum depression (PPD) influences child development and family dynamics. Thus, the general objective of this study is to analyze the implications of PPD on child development and family relationships, with specific objectives: (1) to investigate the effects of postpartum depression on the cognitive and emotional development of the child, (2) to analyze the impacts of postpartum depression on the establishment of the mother-child bond and its effects on family relationships, and (3) to identify risk factors associated with postpartum depression, pointing out support resources and intervention strategies. To achieve this, a bibliographic review of scientific articles and Portable Document Formantt (PDF) books was conducted, analyzing materials from 2014 to 2024, Selected titles and abstracts on the topic under discussion. The findings indicate that PPD directly impacts child development, causing long-term dysfunctional behaviors, difficulties in bonding, impairments in the development of cognitive and affective skills, motor difficulties, and issues with self-esteem. This research is justified as understanding the impacts of PPD is essential for adequate prevention and treatment, promoting better developmental conditions for the child, improved family cohesion, and maternal well-being.